2016
DOI: 10.1080/07391102.2015.1092096
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric site-mediated active site inhibition of PBP2a using Quercetin 3-O-rutinoside and its combination

Abstract: Recent crystallographic study revealed the involvement of allosteric site in active site inhibition of penicillin binding protein (PBP2a), where one molecule of Ceftaroline (Cef) binds to the allosteric site of PBP2a and paved way for the other molecule (Cef) to bind at the active site. Though Cef has the potency to inhibit the PBP2a, its adverse side effects are of major concern. Previous studies have reported the antibacterial property of Quercetin derivatives, a group of natural compounds. Hence, the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Our inverse virtual screening applied in the present study proposes PBP2a to be the most possible target for the flavonoid class of compounds in our library. This in-silico suggestion is supported by a number of previous reports that illustrated flavonoids as possible modifiers of MRSA and other bacterial cell walls [ 18 , 19 , 20 ]. Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our inverse virtual screening applied in the present study proposes PBP2a to be the most possible target for the flavonoid class of compounds in our library. This in-silico suggestion is supported by a number of previous reports that illustrated flavonoids as possible modifiers of MRSA and other bacterial cell walls [ 18 , 19 , 20 ]. Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23).…”
Section: Discussionsupporting
confidence: 78%
“…Surprisingly, this immune active site has a weak point of being under the control of another allosteric site in the same protein, and thus, targeting such a lateral binding site can make MRSA susceptible to their routine antibiotics once again ( Figure 7 ). Previous reports have suggested a number of flavonoids as possible modifiers of MRSA cell wall and cell membrane [ 18 , 19 , 20 ]. Moreover, several polyhydroxylated flavonoids have demonstrated considerable synergistic effect with β-lactams antibiotics [ 16 , 21 ], and PBP2a has been suggested as the possible target [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quercetin-3-rutinoside has been reported to interact with penicillin-binding protein 2a (PBP2a, a cell-wall synthesizing protein), which causes resistivity in methicillin-resistant S. aureus (MRSA) against β-lactam antibiotics [31]. This compound can inhibit PBP2a and thus has the potential to be used in treating MRSA infections [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In case of 3Q6X, active site of the prepared protein was defined as the residues within 10 Å of the reference ligand (ampicillin). In case of protein with no co-crystalized ligand (1 VQQ), the allosteric site was selected and defined from the list of amino acid residues reported in the literature (Kumar et al, 2014 ; Rani et al, 2016 ). The important residues are: Asn146, Ser148, Ser149, Lys148, Lys273, Val277, Gln292, His293, Glu294, Asp295, Tyr297, Arg298, Val299, Thr300, Ile314, Glu315, and Lys316).As a first step, the ability of the docking algorithm was validated to reproduce the co-crystallized pose of ampicillin in the 3Q6X pocket.…”
Section: Methodsmentioning
confidence: 99%